If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4ab + k = 13 Solving 4ab + k = 13 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1k' to each side of the equation. 4ab + k + -1k = 13 + -1k Combine like terms: k + -1k = 0 4ab + 0 = 13 + -1k 4ab = 13 + -1k Divide each side by '4b'. a = 3.25b-1 + -0.25b-1k Simplifying a = 3.25b-1 + -0.25b-1k
| 4x-2+2x+8=9 | | 20x+5p=w | | x^2-x+56=0 | | 11-4a=35 | | 8-8y=5 | | 13-8x=124-29x | | 2x^2-2x+6=0 | | 28a+14=15a-7 | | 4x-1/2=5x | | 0.60X+0.5(10-X)=.10(-39) | | 5-n=-8n | | -2z+8=21+4z | | x-1*x-1= | | y-1=2y-1 | | 12z+6=z-1 | | 8x-40=20x-4 | | 6x+5.5=x+11 | | -17=10u | | 124-7x=11x+18 | | 287-4x=41x+22 | | 6-9x=47-16x | | -x^4+x^3+6x^2-14x+12=0 | | -x^5+3x^4+4x^3-26x^2+40x-24=0 | | m^3+2m-15=0 | | 5x+1=14x-82 | | 8x+4=16-9x | | (x-6)(2x+3)=0 | | 4x^2+22x=-16 | | 8x-12=52 | | 2x+6=x+19 | | 9x-23=58 | | 24x^4-54x=12x^3-27x |